EVENTS BRAND PERSONALITY: INSIGHTS FROM MUSIC FESTIVALS IN PORTUGAL - Gonçalves, Joana; Guerreiro, Manuela; Mendes, Júlio; Pereira, Luís Nobre (Journal of Tourism, Sustainability and Well-being, 2018)
The changing trends in the marketplace and the proliferation of events, have become a reality in which those responsible for managing them seek adequate differentiation strategies through brand management approaches. Although brand personality has been studied in the case of different products, the theory has not been analysed in music festivals contexts. This study aims to analyse what extent is the scale of brand personality developed by Aaker et al. (2001) useful to characterize the brand personality of musical festivals? This research focuses on the study of four of the most iconic music festivals in Portugal: Rock in Rio, MEO Sudoeste, Optimus/NOS Alive and Super Bock Super Rock. Empirical data was collected from university students whose profile matches the profile of the target segments of these four events. This study contributes to the theory as it elaborates on the BP scale in the special case of musical events. It will be also particularly useful to musical events’ organisers as it will enrich their knowledge about the most relevant personality traits that best characterizes this kind of events brands.